2005
DOI: 10.1103/physreve.72.021901
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemical synapses in coupled neurons with noise

Abstract: We examine the behavior in the presence of noise of an array of Morris-Lecar neurons coupled via chemical synapses. Special attention is devoted to comparing this behavior with the better known case of electrical coupling arising via gap junctions. In particular, our numerical simulations show that chemical synapses are more efficient than gap junctions in enhancing coherence at an optimal noise (what is known as array-enhanced coherence resonance): in the case of (nonlinear) chemical coupling, we observe a su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 18 publications
0
28
1
Order By: Relevance
“…This array-enhanced coherence was reported only in the case of linear (diffusive) electrical coupling, mediated by gap junctions between the neurons. The coherence of an array of ML neurons coupled via chemical synapses was studied with changing the noise level in [168]. Results showed that chemical synapses were more efficient than gap junctions in enhancing coherence at optimal noise (known as array-enhanced CR).…”
Section: Noise-induced Resonance and Spatiotemporal Patterns In Neuromentioning
confidence: 98%
“…This array-enhanced coherence was reported only in the case of linear (diffusive) electrical coupling, mediated by gap junctions between the neurons. The coherence of an array of ML neurons coupled via chemical synapses was studied with changing the noise level in [168]. Results showed that chemical synapses were more efficient than gap junctions in enhancing coherence at optimal noise (known as array-enhanced CR).…”
Section: Noise-induced Resonance and Spatiotemporal Patterns In Neuromentioning
confidence: 98%
“…For step 1, a total of 1,000 time series datasets were generated for each synapse type by systematically varying the coupling strength k in the range [1e-4, 0.5] mS/cm 2 , D of both neurons in the range [0, 80], and I dc of both neurons in the range [40,85] (Balenzuela and García-Ojalvo 2005). Only unidirectional couplings were considered.…”
Section: Decision Tree Constructionmentioning
confidence: 99%
“…The coherence of an array of Morris-Lecar neurons coupled via chemical synapses was studied with the noise level changed (Balenzuela and Garcl´a-Ojalvo 2005). Results showed that chemical synapses were more efficient than gap junctions in enhancing coherence at optimal noise (known as arrayenhanced coherence resonance).…”
Section: Introductionmentioning
confidence: 99%